Mini Review on Knowledge Management in Higher Education Challenges and Strategies for Effective Implementation - Muhammad Syihabuddin; Nadia A. Suraj; Selangan E. Hyldgaard; Nisha Kainth (Tinta Emas Institute, 2025)
Knowledge management is a crucial aspect of organizational success in the knowledge-based economy. Unlike information that is only data and facts, knowledge includes perspectives, concepts, and methods that provide added value. This study highlights the importance of knowledge management in higher education, including the acquisition, documentation, transfer, creation, and application of knowledge. Although institutions are active in acquiring knowledge through professional networks and research, reliance on traditional references hinders digital transformation. The lack of structured documentation risks hampering knowledge retention and transfer. Existing knowledge sharing strategies need to be strengthened with internal seminars and group discussions to be more systematic. In addition, the decentralization of innovation and projects requires better coordination through centralized sharing platforms and cross-departmental collaboration. To increase effectiveness, institutions are advised to adopt formal knowledge sharing programs, develop digital repositories, and balance traditional and digital resources to support more optimal learning and innovation.